K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

Ta có:

\(x+y+z=0\)

\(\Rightarrow\left\{{}\begin{matrix}x+y=-z\\y+z=-x\\z+x=-y\end{matrix}\right.\)

\(\Rightarrow\left(x+y\right)\left(y+z\right)\left(z+x\right)=\left(-z\right)\left(-x\right)\left(-y\right)=-xyz=-2020\)

27 tháng 2 2016

x+y+z=0

=>x+y=-z

y+z=-x

z+x=-y

mà A=(x+y)(y+z)(z+x)

nên A=-z*(-x)*(-y)=z*x*y*(-1)=10*(-1)=-10

Vậy A=-10

8 tháng 3 2016

Ta có : \(x+y+z=0\)

=>\(x+y=-z\)

\(y+z=-x\)

\(x+z=-y\)

=> \(B=\left(x+y\right)\left(y+z\right)\left(x+z\right)=\left(-x\right)\left(-y\right)\left(-z\right)=-xyz=-2\)

 

Ta có : x+y+z=0

=>x+y=z

y+z=x

x+z=y

=> B=(x+y)(y+z)(x+z)=(x)(y)(z)=xyz=2


 

Ta có x+y+z=0

\(\Rightarrow x+y=-z\)

\(\Rightarrow x+z=-y\)

\(\Rightarrow y+z=-x\)

Thay vào B ta được B=\(-x.-y.-z=-\left(xyz\right)\)

mà xyz=2 \(\Rightarrow B=-2\)